A Dexamethasone-regulated Gene Signature Is Prognostic for Poor Survival in Glioblastoma Patients. Issue 1 (January 2017) - Luedi, Markus M.; Singh, Sanjay K.; Mosley, Jennifer C.; Hatami, Masumeh; Gumin, Joy; Sulman, Erik P.; Lang, Frederick F.; Stueber, Frank; Zinn, Pascal O.; Colen, Rivka R.
Abstract : Background: Dexamethasone is reported to induce both tumor-suppressive and tumor-promoting effects. The purpose of this study was to identify the genomic impact of dexamethasone in glioblastoma stem cell (GSC) lines and its prognostic value; furthermore, to identify drugs that can counter these side effects of dexamethasone exposure. Methods: We utilized 3 independent GSC lines with tumorigenic potential for this study. Whole-genome expression profiling and pathway analyses were done with dexamethasone-exposed and control cells. GSCs were also co-exposed to dexamethasone and temozolomide. Risk scores were calculated for most affected genes, and their associations with survival in The Cancer Genome Atlas and Repository of Molecular Brain Neoplasia Data databases. In silico Connectivity Map analysis identified camptothecin as antagonist to dexamethasone-induced negative effects. Results: Pathway analyses predicted an activation of dexamethasone network ( z -score: 2.908). Top activated canonical pathways included "role of breast cancer 1 in DNA damage response" ( P =1.07E–04). GSCs were protected against temozolomide-induced apoptosis when coincubated with dexamethasone. Altered cellular functions included cell movement, cell survival, and apoptosis with z -scores of 2.815, 5.137, and –3.122, respectively. CCAAT/enhancer binding protein beta (CEBPB) was activated in a dose dependent manner specifically in slow-dividing "stem-like" cells. CEBPB was activated in dexamethasone-treated orthotopic tumors. Patients with high risk scores had significantly shorter survival. Camptothecin was validated as potential partial neutralizer of dexamethasone-induced oncogenic effects. Conclusions: Dexamethasone exposure induces a genetic program and CEBPB expression in GSCs that adversely affects key cellular functions and response to therapeutics. High risk scores associated with these genes have negative prognostic value in patients. Our findings further suggest camptothecin as a potential neutralizer of adverse dexamethasone-mediated effects. Abstract : Supplemental Digital Content is available in the text.